Effects of Profitability, Liquidity, Capital Structure, and Effects of Covid-19 on Firm Value with Dividend Policy as Intervening Variables (Case Study of Companies Listed on the Indonesia Stock Exchange for the 2018-2021 Period) - Astritta Yahya Kusuma Hayu; Triyono Triyono (ITB AAS Indonesia Surakarta, 2023)
This study aims to determine the effect of Profitability, Liquidity, Capital Structure, and the Covid-19 Pandemic on Firm Value with Dividend Policy as an Intervening Variable. This study used secondary data from 72 companies. It was selected using the sampling method to produce a sample of 20 Food and Beverage companies listed on the Indonesia Stock Exchange for 2018-2021. The research data analysis method uses SPSS v.26 software. The results of this study are that profitability, liquidity, and dividend policy significantly affect firm value. Meanwhile, the indirect effect of liquidity significantly affects financial performance (intervening variable). From the calculation of the Sobel test, it is found that the dividend policy can mediate from liquidity to firm value. Keywords: Return on Assets, Current Ratio, Debt to Equity Ratio, Firm Value, Dividend Policy